Analysis of Upwelling Events and Potential Fishing Grounds for Macarel (Thunnus sp) in the Waters of West Sumatera - Heltria, Septy; Damanik, Ernawati; Lisna, Lisna (Sriwijaya Journal of Environment, 2025)
West Sumatera has high fishery potential, particularly for macarel(Thunnus sp), whose presence is influenced by oceanographic factors such as sea surface temperature (SST), chlorophyll-a concentration, and ocean currents. This study aims to analyze the variability of SST, chlorophyll-a, and currents in West Sumatera waters, identify oceanographic indicators of upwelling events, and examine the relationship between upwelling and potential macarel fishing grounds. Using a qualitative survey approach and ArcGIS 10.8, spatial analysis was conducted to determine potential fishing zones. Results indicate SST fluctuated between 28.1°C (February 2023) and 30,4°C (July 2022), while chlorophyll-a showed seasonal variation, peaking at 0.40 mg/m³ in June 2022. Current patterns are influenced by monsoonal winds and global atmospheric phenomena, with stronger currents during the East season, promoting upwelling and marine productivity. Overlay analysis revealed weak to very weak upwelling occurring periodically. Despite the weak upwelling, West Sumatera remains a highly potential fishing area, supported by positive correlations between SST and chlorophyll-a with macarel fishing zones. Regression analysis shows SST and chlorophyll-a negatively affect macarelcatches, whereas currents have a positive influence. Overall, oceanographic variability significantly impacts fishing potential in West Sumatera.